PENGEMBANGAN MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS GOOGLE SITES DI SMP YAPIS 2 FAKFAK - Rinandi, sita; Nur, Indria; Abdilah, Fardan (Pascasarjana IAIN Sorong, 2024)
The study aims at: (1) developing a learning media of Islamic Education based on Google Sites at Junior High School Yapis 2 Fakfak; (2) analyzing the validity level of the use of learning media of Islamic Education based on Google Sites at Junior High School Yapis 2 Fakfak; and (3) analyzing the effectiveness of the use of learning media of Islamic Education based on Google Sites at Junior High School Yapis 2 Fakfak. The study employed a Research and Development method referring to the 4D model. The subjects for the validity test were media and material expert lecturers. Data were analyzed using qualitative, quantitative, and t-tests. The findings show that: 1) the procedure to develop learning media of Islamic Education based on Google Sites at Junior High School YAPIS 2 Fakfak consists of: a) analyzing learning needs and goals, b) designing Google Sites media, c) developing Google sites media. 2) Results of validation examination of content/material obtained a percentage of 93.8 meaning that it is Strongly Valid, of product design obtained a percentage of 93.8% meaning that it is Strongly valid. The percentage of practicality tests from the small group was 82.2 (very practical), and 83 (very good) from the big group